Pengaruh Penggunaan Model Pembelajaran Kooperatif Tipe Time Token Terhadap Keaktifan Belajar Pendidikan Agama Kristen Siswa Kelas Xl SMK N 1 Siatas Barita Kabupaten Tapanuli Utara Tahun Pembelajaran 2023/2024 - Leonardi Pandiangan; Pestaria Naibaho; Simion Harianja; Albiner Siagian; Oktober Tua Aritonang (Universitas Palan, 2023)
The purpose of this research is to determine the effect of using the Time Token Type Cooperative Learning Model on the Active Learning of Christian Religious Education Students in Class XI of SMK Negeri 1 Siatas Barita. The research method used is a quantitative method and this type of research is pre-experimental design in the form of